Adoption of the principle of ‘Invitation to Treat’ in Islamic law of contracts - Jalil, Md. Abdul (Mind Reader Publications, 2011)
‘Invitation to treat’ looks similar to an offer in a contract but for business convenience and to protect the interests of sellers of goods, the courts differentiated ‘invitation to treat’ from an ‘offer’ on policy grounds. The authors of ‘contract law’ in the UK and other common law countries have analyzed the principle of an ‘invitation to treat’ and have accepted the rationale for its differentiation from an ‘offer’ in contracts. Some Islamic scholars have opposed the differentiation and argued that ‘invitation to treat’ is in fact an offer and when accepted by the offeree, becomes a binding contract. However, their arguments for not accepting the rule of an ‘invitation to treat’ are not very convincing. The purpose of this paper is to put forward the argument that there is an acceptable rationale for differentiating an ‘invitation to treat’ from an offer and to propose that the principle of ‘invitation to treat’ can be adopted in the Islamic law of contract as it does not contradict any shariah (Islamic law) principles. It is to be noted that in this article the English common law principle of ‘invitation to treat’ has been compared with Islamic law of contract. The relevant laws from other common law jurisdictions have not been discussed in this article.